miR-21 promotes the fibrotic properties in oral mucosa through targeting PDCD4 - Yi-Wen Liao; Lo-Lin Tsai; Yu-Hsien Lee; Pei-Ling Hsieh; Cheng-Chia Yu; Ming-Yi Lu (Elsevier, 2022)
Background/purpose: Oral submucous fibrosis (OSF) has been regarded as a premalignant disorder of oral cancer, and myofibroblasts are the main cells that are responsible for pathological fibrosis. Hence, elucidation of the molecular mechanism underlying myofibroblast activation is important to treat OSF. MicroRNA-21 (miR-21) is a well-known fibrosis non-coding RNA, and its role in the development of OSF remains largely unclear. Materials and methods: Luciferase reporter assay was used to confirm the direct interaction between miR-21 and its target programmed cell death 4 (PDCD4). The expression level of PDCD4 in OSF was examined by qRT-PCR. Myofibroblast activities were assessed by collagen gel contraction and transwell migration assays. Results: Our result validated the direct binding of miR-21 to PDCD4. We showed the expression of PDCD4 was downregulated in OSF specimens and negatively correlated with miR-21. Our results suggested that overexpression of PDCD4 in fibrotic buccal mucosal fibroblasts (fBMFs) mitigated the myofibroblast activities, including collagen gel contractility and migration capacity. Moreover, we showed miR-21 contributed to myofibroblast activation of BMFs through repression of PDCD4. Conclusion: Our results suggest that the miR-21/PDCD4 axis mediates the myofibroblast activation of BMFs, and targeting this axis may exert an anti-fibrosis effect.